Clinical Perspective of 3D Total Body Photography for Early Detection and Screening of Melanoma - Rayner, Jenna E.; Laino, Antonia M.; Nufer, Kaitlin L.; Adams, Laura; Raphael, Anthony P; Menzies, Scott W; Soyer, H. Peter (Frontiers in Medicine, 2018)
Melanoma incidence continues to increase across many populations globally and there is significant mortality associated with advanced disease. However, if detected early, patients have a very promising prognosis. The methods that have been utilised for early detection include clinician and patient skin examinations, dermoscopy (static and sequential imaging) and total body photography via 2D imaging. Total body photography has recently witnessed an evolution from 2D imaging with the ability to now create a 3D representation of the patient linked with dermoscopy images of individual lesions. 3D total body photography is a particularly beneficial screening tool for patients at high risk due to their personal or family history or those with multiple dysplastic naevi – the latter can make monitoring especially difficult without the assistance of technology. In this perspective, we discuss clinical examples utilising 3D total body photography, associated advantages and limitations, and future directions of the technology. The optimal system for melanoma screening should improve diagnostic accuracy, be time and cost efficient, and accessible to patients across all demographic and socioeconomic groups. 3D total body photography has the potential to address these criteria and, most importantly, optimise crucial early detection.